Expert Opinion at Crime Scene: An Overview - Pratima Devi Ranga; Yogender Singh (Indian Journal of Forensic Medicine & Toxicology, 2021)
The crime scene is an important place for crime investigation. It often becomes victim of police officers inparticular and general public at large as they are not fully aware of the importance of scientific clue materialswhich will have important impact on the whole process of investigation for successful detection of factsrelating to the offence. Sometimes, it may also so happen that the interested persons knowingly disturbthe crime scene to mislead the investigators. Considering and the evolution of the scientific aspects offorensic science, more attention must be awarded at crime scene to recovering and maintaining the integrityof evidence which will be eventually examined by forensic scientists in the laboratory. As every crimescene is always unique in nature, accordingly a different approach is required for one crime to another. Theopportunity to examine the scene is available only once. If the same is not fully exploited the wealth ofinformation is lost forever. This article focuses on the crime scene management and role of forensic scienceand the laws relating to expert opinion.